A Critical Appreciation of Ken Wilber’s Critique of Eco-Holism - hibbard, whit (The Trumpeter, 2009)
The purpose of this essay is to assess Ken Wilber’s critique of eco-holism or radical ecology. It (a) summarizes Wilber’s integral paradigm, then (b) reviews the eco-holistic paradigm (as interpreted by Wilber), (c) summarizes his critique, (d) reviews the rebuttal and counter-rebuttal, (e) assesses briefly the adequacy of Wilber’s critique, (f) reviews his recommended solution to the ecological crisis, then (g) ends with a rejoinder and conclusion. The focus of this essay is on the question of the potential validity of Wilber’s theoretical model upon which his critique of eco-holism is based. The reason for this focus is that Wilber’s specific criticisms of radical ecology are based on his model. If his model can be shown to be implausible or invalid, then Wilber’s critique of eco-holism is undermined, if not invalidated. On the contrary, if his model is demonstrated to be plausible or potentially valid, his critique must be taken seriously and then evaluated on other grounds, such as its groundedness in the relevant radical ecological literature. The author concludes that Wilber’s all-quadrant all-level model can be accepted as potentially valid. Therefore, his critique of eco-holism is at least potentially valid, but it suffers from a lack of grounding in the radical ecological literature and unjustifiably broad characterizations of eco-holists. From the perspective of his integral vision, Wilber would hope to find an eco-holism that is all-quadrant and all-level; that is, that recognizes, honors, and incorporates the objective, subjective, interobjective, and intersubjective aspects of the developmental levels (holons) within each quadrant. Rather, what he finds is an eco-holism suffering from two partialities: privileging a particular quadrant(s) and privileging a particular level(s).